Class III PI3K Vps34 Controls Thyroid Hormone Production by Regulating Thyroglobulin Iodination, Lysosomal Proteolysis, and Tissue Homeostasis - Grieco, Giuseppina (Thyroid, 2020)
Background: The production of thyroid hormones [triiodothyronine (T3), thyroxine (T4)] depends on the organization of the thyroid in follicles, which are lined by a monolayer of thyrocytes with strict apicobasal polarity. This polarization supports vectorial transport of thyroglobulin (Tg) for storage into, and recapture from, the colloid. It also allows selective addressing of channels, transporters, ion pumps, and enzymes to their appropriate basolateral [Na(+)/I(−) symporter (NIS), SLC26A7, and Na(+)/K(+)-ATPase] or apical membrane domain (anoctamin, SLC26A4, DUOX2, DUOXA2, and thyroperoxidase). How these actors of T3/T4 synthesis reach their final destination remains poorly understood. The PI 3-kinase isoform Vps34/PIK3C3 is now recognized as a main component in the general control of vesicular trafficking and of cell homeostasis through the regulation of endosomal trafficking and autophagy. We recently reported that conditional Vps34 inactivation in proximal tubular cells in the kidney prevents normal addressing of apical membrane proteins and causes abortive macroautophagy. Methods: Vps34 was inactivated using a Pax8-driven Cre recombinase system. The impact of Vps34 inactivation in thyrocytes was analyzed by histological, immunolocalization, and messenger RNA expression profiling. Thyroid hormone synthesis was assayed by (125)I injection and plasma analysis. Results: Vps34 conditional knockout (Vps34(cKO)) mice were born at the expected Mendelian ratio and showed normal growth until postnatal day 14 (P14), then stopped growing and died at ∼1 month of age. We therefore analyzed thyroid Vps34(cKO) at P14. We found that loss of Vps34 in thyrocytes causes (i) disorganization of thyroid parenchyma, with abnormal thyrocyte and follicular shape and reduced PAS(+) colloidal spaces; (ii) severe noncompensated hypothyroidism with extremely low T4 levels (0.75 ± 0.62 μg/dL) and huge thyrotropin plasma levels (19,300 ± 10,500 mU/L); (iii) impaired (125)I organification at comparable uptake and frequent occurrence of follicles with luminal Tg but nondetectable T4-bearing Tg; (iv) intense signal in thyrocytes for the lysosomal membrane marker, LAMP-1, as well as Tg and the autophagy marker, p62, indicating defective lysosomal proteolysis; and (v) presence of macrophages in the colloidal space. Conclusions: We conclude that Vps34 is crucial for thyroid hormonogenesis, at least by controlling epithelial organization, Tg iodination as well as proteolytic T3/T4 excision in lysosomes.